Evaluation of Characteristics of Recycled Asphalt Pavement (RAP) Materials with and without Using Additive Materials - Ebrahim, Soz Muhammed; Karim, Hardy Kamal (Sulaimani Journal for Engineering Sciences, 2019)
Nowadays, reclaimed asphalt pavement is used as hot mix asphalt (HMA) because it has economic and environmental benefits. As an attempt to preserve aggregate resources and save money, this study was done. To evaluate the characteristics of the RAP aggregate, many tests were done that include gradation, specific gravity, Coarse Aggregate Angularity (CAA), Flat and Elongation (F&E), Los Angeles Abrasion (LA), and impact test. Three types of additive materials, which were SBS, CR, and PP, mixed with the reclaimed asphalt blends with three different percentages of 3%, 5%, and 7%. The conventional asphalt binder tests were done for the aged and reclaimed binders. As the percentage of the additive materials increased, the penetration and ductility of the asphalt binder decreased. The elastic recovery of the blends was increased from approximately 7% to 80% when different percentages of SBS additive were used. As the percentage of the additive materials increased, the softening points of the blend increased. The specific gravities of the reclaimed blends were not changed significantly after adding additives. The flash and fire point temperatures increased when the percent of PP additive material was increased to the blends; however, the flash and fire point temperatures decreased when the percent of the SBS and CR additive materials increased. Based on the standard deviation of the RAP asphalt contents, the mixture blend was selected to be 40% RAP and 60% new material. The aged RAP binder was blended with a soft grade virgin asphalt binder that was 60/70 grade. The procedure of Superpave design mixtures was done to find optimum asphalt content and knowing the effects additives on moisture sensitivity of the mixtures. Adding additive materials benefits the reclaimed mixtures regarding moisture sensitivity. The most beneficial effects of additives on moisture sensitivity of the reclaimed mixtures were 7% SBS, 3% CR, and 5% PP obtaining the ITSR of 99.71%, 97.1%, and 90.7%, respectively. The selected most beneficial blends of the reclaimed asphalt binder with additives were further analyzed using Superpave performance grade tests. The additive materials changed the PG of the blended reclaimed binder with no additive materials from 64 -22 °C to PG of over 88-22 °C for 7% SBS, PG of 76-28 °C for 3% CR, and PG of 82-16 °C for 5% PP. It was recommended to use 7% of SBS in the reclaimed asphalt mixtures for hot climates, and 3% of CR for cold climate conditions.
Keywords: RAP; Styrene Butadiene–Styrene (SBS); Crumb Rubber (CR); Recycled Atactic Polypropelene (PP); Performance Grade (PG); Moisture Effect